Suplementasi Folate, Kadar Homocysteine, Nitric Oxide dan Petanda Retinopati Diabetik Studi pada Tikus Sprague Dawley Diabetes - Banundari Rachmawati (MEDIA MEDIKA INDONESIANA, 2012)
Folate supplementation homocysteine, nitric oxide levels and marker for diabetic retinopathy: Study on Sprague Dawley diabetic ratsIntroduction: Diabetic retinopathy (DR) is the leading cause of blindness among diabetes mellitus (DM) patients. Hyperhomocysteinemia (HHcy) is reported to increase the risk for DM complications, however, the underlying mechanism is still unclear. Retina is particularly vulnerable to oxidative stress due to a high demand for oxygen. Hyperglycemia stimulates retinal oxidative stress and increases Nitric Oxide (NO). NO contributes to the regulation of retinal blood vessel function and the occurrence of retinopathy. The administration of folic acid (FA) 0.65 mg/day on HHcy subject, decrease serum Hcy by 42%. This study was aimed to analyze the effect of folate administration on Hcy, NO levels and markers of DR (VEGF serum).Methods: An experimental study using a randomized controlled group pretest posttest design was conducted in UGM Yogyakarta. The total of 40 male Sprague Dawley rats were divided into 5 groups: negative control and the other four group were induced with Streptozotocin 40 mg/kgBW intraperitoneal. Intervention group were given FA 2, 4, 8 ppm through a nasogastric tube for 30 days. Before and after intervention, serum Hcy, NO and VEGF were assessed, and Wilcoxon tests were used to measure the difference ofit.Result: Administration of 8 ppm FA significantly decreased serum Hcy (p=0.043), NO levels (p=0.043) but not for markers of DR.Conclusion: Folic acid supplementation of 8 ppm gives benefits to diabetic rats.Keywords: Diabetic retinopathy, homocysteine, NO, VEGFABSTRAKPendahuluan: Retinopati diabetik (RD) merupakan komplikasi diabetes mellitus yang dapat menjadi salah satu penyebab kebutaan. Hyperhomocysteinemia (HHcy) meningkatkan risiko komplikasi diabetes, namun bagaimana interaksinya masih belum jelas. Retina sangat peka terhadap stres oksidatif karena kebutuhan O2 yang tinggi sedangkan hiperglikemi akan memacu retinal oxidative stres dan peningkatan nitric oxide (NO). NO berperan pada regulasi fungsi pembuluh darah retina dan terjadinya retinopati. Pemberian folic acid (FA) 0,65 mg/hr pada subyek HHcy menurunkan Hcy serum 42%. Tujuan penelitian ini adalah menganalisis pengaruh pemberian folate terhadap kadar Hcy, NO dan petanda RD (VEGF serum)Metode: Penelitian ini bersifat eksperimental dengan rancangan randomized controlled group pretest posttest design. Penelitian dilakukan di LPPT unit IV UGM Yogyakarta. Sampel 40 tikus Sprague Dawley jantan, umur 2-3 bulan, BB 190-275 g dibagi 5 kelompok: kelompok kontrol negatif dan 4 kelompok lain diinduksi dengan STZ 40mg/kgBB intra peritoneal. Kelompok intervensi diberi FA 2, 4, 8 ppm (sonde) selama 30 hari. Kemudian diperiksa kadar Hcy, VEGF, NO serum. Perbedaan parameter sebelum dan sesudah intervensi dianalisis dengan uji Wilcoxon.Hasil: Pemberian FA 8 ppm menurunkan secara bermakna kadar Hcy (p=0,043), NO serum (p=0,043) dan tidak menurunkan petanda RD (VEGF serum) secara bermakna.Simpulan: Pemberian FA 8 ppm bermanfaat pada tikus diabetes.